What is the crisis? Defining and prioritizing the world's most pressing problems. Issue 9 (1st November 2008) - Cabrera, Derek; Mandel, James T; Andras, Jason P; Nydam, Marie L
Abstract : As consensus grows regarding the unprecedented global environmental challenges we currently face, so too does the notion that publicly funded science has a duty to dedicate resources toward overcoming these challenges. In order for scientists to shift attention and resources to the most pressing global problems, we must first enumerate these issues and establish consensus across academia as to the importance and feasibility of solving them. To this end, we have applied concept mapping to a large and diverse pool of disciplinary experts – the entire faculty of Cornell University – to empirically assess their opinions on what our most pressing global crises are, how they relate to one another, and how feasible it would be to solve them. We (1) define what Cornell University faculty see as the most pressing problems of our day, (2) sort them into relevant, modern "disciplines", and (3) rate them according to both their importance and the feasibility of solving them. This study reveals broad consensus across disciplines, groups global crises into seven thematic clusters that cross disciplinary boundaries, and rates issues relevant to all disciplines on a scale of importance and solvability. We believe that this provides a structured framework for both the scientific community and the global community to address global crises.